2008
DOI: 10.1029/2007je002941
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of the Martian south polar layered deposits: MARSIS data inversion using Bayesian inference and genetic algorithm

Abstract: [1] Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) has offered abundant data, which have been used to estimate dielectric properties of the south polar layered deposits (SPLD) of Mars. This paper presents a new way to invert the data to estimate the dielectric properties of the SPLD. A total of 4364 measurements were analyzed. The received radar signals are controlled by the physical properties of the SPLD and its basal layer and in addition by a number of factors including the transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Also in this case, modelling assumed a plane electromagnetic wave propagating normally through three homogeneous non-magnetic layers. In their analysis, Zhang et al (2008) found a large sensitivity of the solution to small changes in initial conditions, making this an ill-posed problem. It was found that the most probable value of the relative dielectric constant of the SPLD lay between 3.0 and 5.0, and that the relative dielectric constant of the basal layer was between 7.5 and 8.5, a value typical of basalts.…”
Section: Marsis Signal Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in this case, modelling assumed a plane electromagnetic wave propagating normally through three homogeneous non-magnetic layers. In their analysis, Zhang et al (2008) found a large sensitivity of the solution to small changes in initial conditions, making this an ill-posed problem. It was found that the most probable value of the relative dielectric constant of the SPLD lay between 3.0 and 5.0, and that the relative dielectric constant of the basal layer was between 7.5 and 8.5, a value typical of basalts.…”
Section: Marsis Signal Inversionmentioning
confidence: 99%
“…The ratio between subsurface and surface reflections over a portion of the SPLD was used also by Zhang et al (2008) to develop a different approach to inversion, based on Bayesian inference. Through the parametric forward modelling of propagation through the SPLD and the derivation of the statistical distribution of subsurface-to-surface echo power ratio, they applied a genetic algorithm to estimate the most likely set of physical parameters producing the observed echoes.…”
Section: Marsis Signal Inversionmentioning
confidence: 99%
“…[6] Determination of subsurface dielectric permittivity through the inversion of the radar echo is an approach to determine subsurface composition and has been used for MARSIS observations in a limited number of cases [e.g., Picardi et al, 2008;Zhang et al, 2008]. We present a somewhat simplified inversion method to find the dielectric properties at the base of the North PLD's.…”
Section: Introductionmentioning
confidence: 99%
“…Such an ill-posed inverse problem has been solved for MARSIS observations in a limited number of cases [10] [11]. In this work, we present a simple inversion method and demonstrate its effectiveness in the investigation of the dielectric properties at the base of the South PLD's.…”
Section: Introductionmentioning
confidence: 98%